ORGANIC FERTILIZER FROM TECHNOGENIC COAL WASTE – IN ISSUES OF SOIL FERTILITY AND YIELD PRODUCTIVITY - Yakubov Salimjon Iminzhanovich; Sarynsakhodzhaev Askar Rakhmetkhodzhaevich; Yunusova Farida Rakhmonberdievna; Irmuhamedova Lyudmila (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
One of the man-made formations during coal mining at the Angrensky open-pit mine is coal-containing waste. Such carbon-containing wastes are excellent resources for producing organic fertilizers. The agricultural sector of Uzbekistan is developing rapidly, and issues of soil fertility are becoming more pressing. The article discusses some aspects, in particular organo-mineral fertilizers obtained from technogenic carbon-containing waste. The results of agrochemical research, the technological possibility of obtaining a pilot batch of organic fertilizer “Superhumus” on the field conditions of the production site of the Angrenskaya lignite open-pit mine are presented.